Receipt of Proton-Pump Inhibitors during Pregnancy and Risk for Preeclampsia - Bello, Natalie A.; Huang, Yongmei; Syeda, Sbaa K.; Wright, Jason D.; D'Alton, Mary E.; Friedman, Alexander M. (American Journal of Perinatology, 2020)
Objective This study aimed to determine whether receiving a proton-pump inhibitor (PPI) prescription during pregnancy was associated with decreased risk for preeclampsia.Study Design The Truven Health MarketScan database was used to determine whether receiving a PPI prescription was associated with risk for preeclampsia. Risk for preeclampsia was evaluated based on the presence or absence of receiving a PPI prescription (1) any time during pregnancy, and 2) individually during the 1st, 2nd, and 3rd trimesters. In addition to evaluating risk for all preeclampsia, severe preeclampsia and preterm severe preeclampsia were evaluated. Adjusted models including risk factors such as chronic hypertension, maternal age, multiple gestation, and diabetes were performed with adjusted risk ratios (aRR) with 95% confidence intervals [CIs] as measures of effect.Results A total of 2,755,885 women were included in the analysis of whom 69,249 were prescribed a PPI during pregnancy (2.5%). In adjusted models, receiving a PPI prescription anytime during pregnancy (aRR 1.28, 95% CI 1.24–1.32), the 1st trimester (aRR 1.12, 95% CI 1.04–1.22), the 2nd trimester (aRR 1.20, 95% CI 1.15–1.26), and the 3rd trimester (aRR 1.41, 95% CI 1.35–1.47) were all associated with increased risk for preeclampsia. Risk for severe preeclampsia was also significantly increased with receiving a PPI prescription anytime during pregnancy (aRR 1.21, 95% CI 1.15–1.27), during the 2nd trimester (aRR 1.14, 95% CI 1.06–1.23), and during the 3rd trimester (aRR 1.33, 95% CI 1.24–1.43), but not the first trimester (aRR 1.04, 95% CI 0.92–1.19). Evaluating the risk for preterm severe preeclampsia, adjusted risk was significantly increased with receiving a PPI prescription in the second trimester (aRR 1.35, 95% CI 1.21–1.52) but not the first trimester (aRR 1.06, 95% CI 0.86–1.32).Conclusion In this analysis of payer data, receiving a PPI prescription during pregnancy was not associated with decreased risk for preeclampsia. Further empiric research is required to determine whether an effect may be present.Key Points
Keywords: proton-pump inhibitors; preeclampsia; preeclampsia prevention